Decolonizing the past: Integrating the 'practical past' and local literature in Southeast Asian primary history education - Mujahidin Farid; Styo Mahendra Wasita Aji (Privietlab, 2025)
The​‍​‌‍​‍‌ history curriculum in primary schools across Southeast Asia frequently continues to be the inheritance of colonialism, which means that it is dominated by a Western-derived, evidence-based